STUDY OF IMPROVING PERFORMANCE OF RAPID TRANSIT (BRT) BUS IN YOGYAKARTA - Samad, Abdul; Wicaksono, Achmad; Sulistyo, Harnen; Djakfar, Ludfi (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2019)
The implementation of the Rapit Transit Bus (BRT) requires evaluation of performance, by exploring service quality. Because service quality is important for the success of Trans Jogja. The purpose of this study was to determine the existing conditions of bus rapid transit (BRT) service and performance in the city of Yogyakarta, and to find out the priority strategies for implementing bus rapid transit (BRT) management at the study site. Â The method used in this study was the Science and QFD methods. The results of the research on the existing level of BRT performance in Yogyakarta, the arrival and departure times of Trans Jogja buses are good and can satisfy passengers, but the waiting time and operating time still need handling. The research results of the priority strategies for implementing BRT management management that need to be addressed are ease of location from the community living environment to the Trans Jogja bus stop, ease of change of mode, and management of cost compliance.